Determination of the presence of huanglongbing in seeds and movement of the pathogen in Citrus reticulata - Shokrollah, Hajivand; Abdullah, Thohirah Lee; Sijam, Kamaruzaman; Abdullah, Siti Nor Akmar (Science Publications, 2009)
Problem statement: Huanglongbing (HLB) also known as citrus greening disease is a fastidious phloem-inhabiting bacterium in the genus Candidatus Liberibacter. Using universal primers, the 16S ribosomal DNA sequence of three strains of the bacterium were obtained by PCR. However there is very little information on seed transmission and HLB pathogen movement to find a way for control or reduce the severity of HLB on the field. The study was conducted to detect HLB pathogen in seeds of Citrus, to determine pathogen movement in citrus seedling after infection and to detect the HLB pathogen in citrus roots. Approach: Seeds of Citrus reticulata cv. Limau Madu were collected from infected orchard and were germinated in screenhouse condition. The seeds of Citrus reticlata cv. L. Madu were planted in screenhouse too for HLB pathogen movement and HLB detection in roots. The seedlings were inoculated using infected grafting methods. Results: HLB was not amplified in new seedlings after germination. HLB moved slowly reaching up to 1.5 cm after 2 weeks, 1.5-4.5 cm after eight weeks and detected on 4.5-9 cm after 14 weeks below the grafting area. HLB was also detected up to 9-15 cm after 16 weeks, 15-24 cm after twenty weeks, 24-28.5 cm after 22 weeks and 28.5-30 cm after 24 weeks below the grafting area. Conclusion: Base on conventional PCR test, HLB disease in citrus is not seed borne and it can reach to the roots 26 weeks after inoculation.